2017
DOI: 10.1016/j.metabol.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute fasting inhibits central caspase-1 activity reducing anxiety-like behavior and increasing novel object and object location recognition

Abstract: Background Inflammation within the central nervous system (CNS) is frequently comorbid with anxiety. Importantly, the pro-inflammatory cytokine most commonly associated with anxiety is IL-1β. The bioavailability and activity of IL-1β is regulated by caspase-1-dependent proteolysis vis-a-vis the inflammasome. Thus, interventions regulating the activation or activity of caspase-1 should reduce anxiety especially in states that foster IL-1β maturation. Methods Male C57BL/6j, C57BL/6j mice treated with the capas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 91 publications
2
6
0
Order By: Relevance
“…Here we show that overnutrition following IF in the form of a HFD-refeed can impair mouse memory/learning in as little as 2 h. The present model was used to model spontaneous ab-lib consumption of food following IF, which is germane to many current CRbased weight loss/control approaches n [38]. In our previous work, we found that mice fasted for 24 h have improved cognition and decreased caspase-1 activity in the brain [15]. From a teleological standpoint, this hunger-associated enhancement in learning/memory is not surprising in that nutritional stress should be motivating and assist in foraging and/or food-finding behaviors.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Here we show that overnutrition following IF in the form of a HFD-refeed can impair mouse memory/learning in as little as 2 h. The present model was used to model spontaneous ab-lib consumption of food following IF, which is germane to many current CRbased weight loss/control approaches n [38]. In our previous work, we found that mice fasted for 24 h have improved cognition and decreased caspase-1 activity in the brain [15]. From a teleological standpoint, this hunger-associated enhancement in learning/memory is not surprising in that nutritional stress should be motivating and assist in foraging and/or food-finding behaviors.…”
Section: Discussionmentioning
confidence: 76%
“…As we have previously shown, acute fasting improves mouse memory while reducing caspase-1 activity in the brain [15]. Due to the well-recognized role of IL-1β in learning and memory [16], activation of caspase-1 in the CNS appears critical to the impact of stress on cognition [17,18].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations